A Study of women career in construction industry - Nurul Norliana, Salahuddin (2015)
The achievement of women in different field in Malaysia is no more hesitating which they can compete with men in the construction industry field. There are misconceptions that women are weak and unable to be good leader or workers as compared to men. Other than that, there are many obstacles that exist for women who want to work in the construction industry. Women need to be prepared in terms of profound knowledge, expertise, work encounters and the willingness to comply at the work environment. The main problem that encountered by women when they are involved in the construction industry is risk and conflict. Besides that, the scope of appropriate work for women in construction industry or field is identified. In addition, this research was carried out through a literature review of the topics that related to the factors that led to the liability and conflict that come upon by women as workers in the construction industry or fields. The masculinity and feminization of construction engineering, sex discrimination and harassment on site, work environment and work hours and intellectual and physical capability is the main factors that led to challenges and risks for women working in the construction field are. In this research the 100 questionnaires were distributed to women and men who working in the construction industry which is currently developing construction project such as Kuala Lumpur, Johor, Penang and Pahang and were selected through simple random sampling method but only 68 questionnaires have been completed by the respondents. All data was analysed using software Statistical Package for Social Science 22 (SPSS) to acquire min statistic and standard deviation. From the questionnaire, it found that female and male have different levels or agreement with all factors of risk and conflict that encountered. This research will be supportive to any women in identifying the most suitable careers for themselves in construction industry or field and also to know the factors that cause fewer women working in the construction industry or field.